Family Financial Education and Financial Literacy: Improving Personal Financial Management for Generation Z Students - Pratama, Wilson Candra Teguh; Ramlah, Sri; Barokah, Siti (Westscience Press, 2025)
Digital technology's quick development has changed how people may obtain financial data, which presents Generation Z with both benefits and difficulties when it comes to handling their own affairs. The purpose of this study is to investigate experimentally how financial literacy and family financial education affect the personal financial management of Indonesian university students in Generation Z. Using a quantitative methodology, 100 undergraduate management students from Universitas Muhammadiyah Gombong and Universitas Putra Bangsa Kebumen were chosen by non-probability sampling and given online questionnaires to complete in order to gather primary data. Multiple linear regression analysis, traditional assumption testing, and validity and reliability testing were all part of the data analysis process. The findings indicate that while financial literacy has a good and significant influence on students' personal financial management, family financial education has no discernible effect. The two variables taken together account for 48% of the variation in personal financial management, with other factors not included in this study influencing the other 52%. In order to promote sound financial decision-making in the digital age, educational institutions and policymakers should concentrate on bolstering financial literacy programs in addition to family-based financial education, as these findings demonstrate the significant influence of financial literacy in forming Generation Z students' prudent financial behavior.